Diabetic Retinopathy Screening and Monitoring of Early Stage Disease in Australian General Practice: Tackling Preventable Blindness within a Chronic Care Model. (20th December 2015) - Crossland, Lisa; Askew, Deborah; Ware, Robert; Cranstoun, Peter; Mitchell, Paul; Bryett, Andrew; Jackson, Claire
Abstract : Introduction . Diabetic retinopathy (DR) is the leading cause of preventable blindness in Australia. Up to 50% of people with proliferative DR who do not receive timely treatment will become legally blind within five years. Innovative and accessible screening, involving a variety of primary care providers, will become increasingly important if patients with diabetes are to receive optimal eye care. Method . An open controlled trial design was used. Five intervention practices in urban, regional, and rural Australia partnered with ophthalmologists via telehealth undertook DR screening and monitoring of type 2 diabetes patients and were compared with control practices undertaking usual care 2011–2014. Results . Recorded screening rates were 100% across intervention practices, compared with 22–53% in control practices. 31/577 (5%) of patients in the control practices were diagnosed with mild-moderate DR, of whom 9 (29%) had appropriate follow-up recorded. This was compared with 39/447 (9%) of patients in the intervention group, of whom 37 (95%) had appropriate follow-up recorded. Discussion and Conclusion . General practice-based DR screening via Annual Cycle of Care arrangements is effective across differing practice locations. It offers improved recording of screening outcomes for Australians with type 2 diabetes and better follow-up of those with screen abnormalities.